(untitled) (Global Scientific Review, 2022)
Cultivation of oil sunflower varieties as the main and repeated crops in Uzbekistan has been increasing in recent years. Sunflower seeds are the main source of high-quality lipids and proteins. In 2022, 45,000 tons of vegetable oil and 83,000 tons of sunflower meal will be produced in Uzbekistan. Currently, the production of sunflower oil in the world is mainly carried out by high temperature pressing and extraction with organic solvents. But the traditional processing technology of sunflower seeds has clear disadvantages. For example, at a high temperature, the acidity of vegetable oil increases, and the protein in the vegetable oil is denatured. Therefore, it is necessary to improve the quality of sunflower oil and protein flour and to increase the level of complex processing in order to ensure the food safety of the oil and the healthy nutrition of people. The article describes the plan for processing this complex and the results expected from it